2018
DOI: 10.3390/ijms20010090
|View full text |Cite
|
Sign up to set email alerts
|

In-Cell NMR Study of Tau and MARK2 Phosphorylated Tau

Abstract: The intrinsically disordered protein, Tau, is abundant in neurons and contributes to the regulation of the microtubule (MT) and actin network, while its intracellular abnormal aggregation is closely associated with Alzheimer’s disease. Here, using in-cell Nuclear Magnetic Resonance (NMR) spectroscopy, we investigated the conformations of two different isoforms of Tau, Tau40 and k19, in mammalian cells. Combined with immunofluorescence imaging and western blot analyses, we found that the isotope-enriched Tau, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…In-cell NMR has over the years evolved into a well-established, valuable tool to study proteins in close-to-native conditions ( Serber and Dötsch, 2001 ; Montheith and Pielak., 2014 ; Theillet et al, 2016 ; Luchinat and Banci., 2018 ). Until now, only a single study has been published on in-cell NMR experiments of tau protein, focusing on a shorter fragment ( Zhang et al, 2018 ). In this work, the authors acquired 2D HSQC spectra of the 15 N-labelled K19 fragment in several buffer conditions and subsequently, upon electroporating the protein into HEK-293 cells.…”
Section: Monomeric State As the Starting Point Of Tau Self-assemblymentioning
confidence: 99%
“…In-cell NMR has over the years evolved into a well-established, valuable tool to study proteins in close-to-native conditions ( Serber and Dötsch, 2001 ; Montheith and Pielak., 2014 ; Theillet et al, 2016 ; Luchinat and Banci., 2018 ). Until now, only a single study has been published on in-cell NMR experiments of tau protein, focusing on a shorter fragment ( Zhang et al, 2018 ). In this work, the authors acquired 2D HSQC spectra of the 15 N-labelled K19 fragment in several buffer conditions and subsequently, upon electroporating the protein into HEK-293 cells.…”
Section: Monomeric State As the Starting Point Of Tau Self-assemblymentioning
confidence: 99%
“…Time-resolved in-cell NMR demonstrated that Tyr125 phosphorylation was selectively impaired by the C-terminal methionine oxidation, suggesting that alteration of the cellular environment can selectively affect post-translational modifications of α-synuclein and, thus, potentially control its conformation, conformational landscape, and aggregation propensity [ 42 ]. Isotope-enriched Tau was delivered into HEK-293T cells by electroporation and the NMR spectrum of Tau in living cells was acquired [ 43 ]. It was found that Tau predominantly binds to microtubules (MT) at its MT-binding repeats in HEK-293T cells.…”
Section: In-cell Study Of Protein Folding Using Biophysical Probesmentioning
confidence: 99%
“…It was found that Tau predominantly binds to microtubules (MT) at its MT-binding repeats in HEK-293T cells. It was also found that disease-associated phosphorylation of Tau was immediately eliminated once phosphorylated Tau was delivered into HEK-293 T cells, implying a potential cellular protection mechanism under stressful conditions [ 43 ].…”
Section: In-cell Study Of Protein Folding Using Biophysical Probesmentioning
confidence: 99%
“…With the development of modern biotechnology, increasing numbers of researchers are conducting molecular biology research pertaining to the environmental adaptability of this mammal. In the last few years, high-throughput studies on yaks, such as genome and miRNA sequencing and transcriptome analysis, have become popular 13 15 . In fact, there are still many unexplored areas of basic research in this animal.…”
Section: Introductionmentioning
confidence: 99%